An Integrative Model of Green Sustainable Science, Environmental Awareness, and Eco-Friendly Practices in Community Life - Md Masud Morshed (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: Sustainable community life requires aligning scientific knowledge, environmental awareness, and daily eco-friendly behavior. However, the connection between what communities know, believe, and practice often remains inconsistent. This study aims to examine how Green Sustainable Science is integrated into community life, assess environmental awareness levels, and identify environmentally friendly practices that support sustainability in daily activities. Methodology: This study used a qualitative case study approach. Data were collected through in-depth interviews, participatory observation, and documentation. The instruments included semi-structured interview guides, observation sheets, and documentation notes. Data analysis employed the Miles and Huberman interactive model with reduction, display, and conclusion stages. Main Findings: Findings show that sustainability concepts have been integrated into community routines, although understanding varies and tends to be practical in nature. Environmental awareness ranges from moderate to high among active groups but remains inconsistent in others. Eco-friendly behaviors such as waste sorting, reducing plastic use, and saving energy are present but constrained by limited facilities and policy support. These findings reveal that sustainable behavior emerges from the interaction between knowledge, awareness, and structural conditions, highlighting the need for stronger community programs and better environmental infrastructure. Novelty/Originality of this study: This study provides new insights into how communities integrate sustainability concepts beyond formal education and policy frameworks. Its originality lies in examining the direct link between scientific knowledge, awareness, and daily life practices. The findings contribute to advancing strategies for community empowerment and contextual environmental programs.